2012
DOI: 10.1017/s002193201200020x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Consanguineous Marriages in South Sinai, Egypt

Abstract: Summary. A total of 3961 married couples from six major geographical areas representing the South Sinai governorates in Egypt were studied to assess the rate of consanguineous marriage. The population of six selected areas (St Catherines, Nuweiba, Abu Rudeis, Ras Sudr, El Tor and Abu Zenima) were subdivided into Bedouin, urban and mixed populations. A questionnaire-based interview was conducted showing that the consanguinity rate in this region is 37.5%, with the highest rate recorded in Abu Rudeis (52.3%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 19 publications
(31 reference statements)
0
14
0
1
Order By: Relevance
“…In the emerging EMR market-nations, a combination of various causes of FLV is noted. Additional factors contributing to the intricacy of FLV in children are the high rate of consanguineous marriages, unacceptable therapeutic abortions, and the high birth rates 2930313233. Improved access to health care and improved delivery of health care especially related to maternal and child health care in most of the aforementioned countries have resulted in better survival of preterm children.…”
Section: Causes Of Childhood Blindness and Visual Impairmentmentioning
confidence: 99%
“…In the emerging EMR market-nations, a combination of various causes of FLV is noted. Additional factors contributing to the intricacy of FLV in children are the high rate of consanguineous marriages, unacceptable therapeutic abortions, and the high birth rates 2930313233. Improved access to health care and improved delivery of health care especially related to maternal and child health care in most of the aforementioned countries have resulted in better survival of preterm children.…”
Section: Causes Of Childhood Blindness and Visual Impairmentmentioning
confidence: 99%
“…4,5 A report by the Dubai-based Centre for Arab Genomic Studies (CAGS) in September 2009 found that many Arab countries display one of the highest rates of consanguineous marriage and genetic disorders, nearly two-thirds of which are linked to consanguinity. Research from CAGS and others suggests consanguinity is declining in Lebanon, 17,18 Egypt, 16,19 Bahrain, 20 and among Palestinians, 13,21 but is increasing in Qatar, 10,22 Yemen, 14,15 United Arab Emirates, 11,12 Morocco, Mauritania and Sudan. 4 Qatar was the last Arab Gulf state to institute mandatory screening in 2009, mainly to warn related couples who are planning marriage about any genetic risks they may face.…”
Section: Introductionmentioning
confidence: 98%
“…It has often been favored because it is believed to protect tribal traditions, cultural values from changes through many generations, preserve familial wealth, strengthen family ties, promote family stability, and the region's expanding economies, taking advantages relating to reduction of dowry or bride price or bride wealth payment requirements. 5,19,30 Other reasons may include geographic proximity, keeping and strengthening family's structure and ties, a closer relationship between the wife and her in-laws. 5,19,30,31 Also it is thought to have some protective role(s) against divorce and increase survival of marriages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of consanguineous marriage, particularly on fertility, mortality, and morbidity, have since a long time been of a great interest to doctors and geneticists. That has led to an abundance of publications since the end of the 20th century [4,[7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%